2021
DOI: 10.1021/acs.energyfuels.1c01461
|View full text |Cite
|
Sign up to set email alerts
|

A Novel MoS2-MXene Composite Cathode for Aluminum-Ion Batteries

Abstract: Metal dichalcogenide cathodes can be used to increase the capacities of rechargeable aluminum-ion batteries. However, the higher charge density of trivalent metal cations (Al3+) and the inherently strong polarization effect on the host lattice result in poor MoS2 cycling performance. Thus, we designed MoS2-MXene composites as a novel cathode to improve the performance of rechargeable aluminum-ion batteries. The results of this study show that Ti3C2T x MXene can provide a conductive framework with exceptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 22 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…The WS 2 /WO 3 electrodes delivered the capacity of 225, 152, 108, 86, and 74 mAh/g at 1000−5000 mAh/g, while the WS 2 electrodes only maintained 186, 112, 78, 62, and 34 mAh/g under the same conditions. In addition, we compare the cycling performance with the literature for AIB cathodes in Figure 7c, such as MoS 2 @ rGO, 21 MoS 2 @MXene, 22 CoSe/CND, 23 Co 3 O 4 , 12 and G- VS 2 . 8 The larger specific surface area can provide more active sites for the WS 2 /WO 3 electrodes, and the introduction of the WS 2 /WO 3 heterojunctions can accelerate the electron transfer rate between the interfaces, in which the cooperation between them endows the WS 2 /WO 3 electrodes with excellent cycling and rate performance.…”
Section: Crystal Structure and Microscopic Morphologymentioning
confidence: 99%
“…The WS 2 /WO 3 electrodes delivered the capacity of 225, 152, 108, 86, and 74 mAh/g at 1000−5000 mAh/g, while the WS 2 electrodes only maintained 186, 112, 78, 62, and 34 mAh/g under the same conditions. In addition, we compare the cycling performance with the literature for AIB cathodes in Figure 7c, such as MoS 2 @ rGO, 21 MoS 2 @MXene, 22 CoSe/CND, 23 Co 3 O 4 , 12 and G- VS 2 . 8 The larger specific surface area can provide more active sites for the WS 2 /WO 3 electrodes, and the introduction of the WS 2 /WO 3 heterojunctions can accelerate the electron transfer rate between the interfaces, in which the cooperation between them endows the WS 2 /WO 3 electrodes with excellent cycling and rate performance.…”
Section: Crystal Structure and Microscopic Morphologymentioning
confidence: 99%
“…However, the reported graphite-based cathodes have intrinsically low storage capacities (60-175 mAh g −1 ) [13][14][15][16][17][18][19] due to the solvated ion (AlCl 4 − ) intercalation mechanism, rather than multivalent ion (Al 3+ ) transformation. More recently, extensive efforts have been made to develop new cathode materials to promote the specific/volumetric capacity of AIBs, including transition metal oxides, [20][21][22][23][24] sulfides, [25][26][27][28][29][30][31][32][33][34][35][36][37][38] selenides, [39][40][41][42][43][44][45][46][47] and others. [48][49][50] For example, Zhang et al [47] reported SnSe nanoparticles as cathode materials with a high initial discharge capacity of 582 mAh g −1 at a current density of 300 mA g −1 and this cathode material provided 107 mAh g −1 reversible capacity after 100 cycles and had a discharge voltage of 1.6 V (vs Al/AlCl 4 − ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the restacking phenomenon among interlaminar nanosheets blocks the surface accessibility and ion storage . To bridge the above-mentioned gaps, the incorporation of low-dimensional materials and conductive or active additives (graphene, black phosphorus, and PEDOT:PSS) can accelerate the electron conduction and ion diffusion . For example, Gao et al reported the Ti 3 C 2 T x /GO fiber, which had an enhanced capacitance of 586.4 F cm –3 .…”
Section: Introductionmentioning
confidence: 99%